2009
DOI: 10.1002/ajmg.a.32663
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome 10 variant with a 12 Mb inversion [inv(10)(q11.22q21.1)] identical by descent and frequent in the Swedish population

Abstract: We identified a paracentric inversion of chromosome 10 [inv(10)(q11.22q21.1)] in 0.20% of Swedish individuals (15/7,439) referred for cytogenetic analysis. A retrospective analysis of 8,896 karyotypes from amniocenteses in Sweden revealed a carrier frequency of 0.079% (7/8,896) for the inversion. Cloning and detailed analysis of the inversion breakpoint regions show enrichment for interspersed repeat elements and AT-stretches. The centromeric breakpoint coincides with that of a predicted inversion from HapMap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, no clear relationship between clinical symptoms and chromosomal abnormality was found [Entesarian et al, 2009]. We believe that probably in our family an association between the presence of the inversion and intellectual disability exists.…”
Section: Discussionmentioning
confidence: 57%
“…However, no clear relationship between clinical symptoms and chromosomal abnormality was found [Entesarian et al, 2009]. We believe that probably in our family an association between the presence of the inversion and intellectual disability exists.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to these common variants, numerous rare and unique inversions have been observed in individuals with no apparent phenotype. An illustrative example is inv(10)(q11.22q21.1), a 12 Mb inversion with a carrier frequency of 0.11% in the Swedish population, but with no consistent phenotype [19]. Breakpoint and haplotype analysis indicated that this is a rare variant in the population, originating from a single founder event.…”
Section: Cytogenetically Visible Inversionsmentioning
confidence: 99%
“…The role of the chromosomal inversions in adaptation and evolution of different Drosophila species has been studied for several decades [3][4][5]. More recently, genome sequencing and mapping revealed functionally important inversions in the human genome [6][7][8][9][10]. Polymorphic inversions have been shown to be associated with epidemiologically important phenotypes in Afrotropical populations of Anopheles [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%